PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI KANTOR WILAYAH DJBC JAWA TIMUR I DENGAN KOMPETENSI SEBAGAI VARIABEL MEDIASI - Wibowo, Edy Dwi; Rahayu, Sri; Fitrianty, Rifda (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effects of training and career development on employee performance, with competence as a mediating variable, at customs and excise regional office I of east java. The study employed a quantitative explanatory approach using a survey method. The population and sample consisted of 194 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results show that training and career development have positive and significant effects on competence. Competence, training, and career development also have positive and significant effects on employee performance. Competence significantly mediates the effect of training on employee performance and the effect of career development on employee performance. Both mediating relationships indicate complementary partial mediation. Training has the strongest direct effect on employee performance. These findings highlight the importance of applicable training, well-directed career development, and continuous competence enhancement in improving employee performance.